Full protection and security in International Law - Magnusson, Finnur (Universität Wien, 2012)
The thesis covers one of the investment standards of international investment law, namely the full protection and security standard. In Part I, the study is introduced in terms of structure and substance. Chapter 1 provides a description of the scope of the research topic and a definition of its terms and structure. Chapter 2 covers the historical development of the full protection and security standard. Part II deals with three fundamental issues concerning the standard: sources, interpretation and content. Chapter 3 contains a discussion dealing with the various sources of the standard. Each source will be studied independently. Chapter 4 will address general issues with regard to interpretation, such as to what extent the Vienna Convention on the Law of Treaties influences the process of interpretation. Chapter 5 deals with the content of the standard of full protection and security, including conceptual issues relating to the substantive elements of which the standard consists. Moreover, the chapter will ask questions as to which underlying issues are needed to explore when a due diligence assessment is made in order to determine whether a state has fulfilled its obligations to provide protection and security. Part III deals with issues relating to the violations of the standard. In Chapter 6, the violations of the standard and their many manifestations will be analyzed. The chapter will address whether certain fact-based scenarios can be established in which the standard is most commonly violated. Finally, Chapter 7 contains a summary of findings.
Keywords: Arbitral Awards; Bilateral Investment Treaties (BITs); Due diligence; Full protection standard; Full security standard; ICSID; International Investment Law; International law; Investment standards; Investments

Public assets financing in Nigeria : the imperatives for legal reforms to unlock domestic financial resources and foreign capital for infrastructure development - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2012)
Infrastructure is one of the main parameters of economic growth and a country‘s competitiveness depends on the provision and maintenance of efficient and productive infrastructure assets. However, Nigeria, like most countries in Sub-Saharan Africa has the lowest quantity and poorest quality of stocks of infrastructure assets in the world and this phenomenally poor infrastructure has remained an impediment to development in the country. Decades of sub-optimal investment, poor maintenance culture and the fact that the required infrastructure investments could not be accommodated within the available fiscal space as a result of budgetary constraints have all contributed to the Nigeria‘s infrastructure deficit. The immediate outcome of this however is that the available infrastructure assets across the Nigerian landscape are in decrepit state and absurdly inadequate. Besides, the present demand for basic infrastructure services has grown astronomically out-stripping the supply capacity of the existing ones. Closing the infrastructure financing gap will however require increased investment by private investors through creative financing in an enabling legal and financial environment. Outside the budgetary constraints, the absence of efficient maintenance and management of infrastructure assets and quality service delivery by the public sector are some of the reasons why procurement of public infrastructure stocks by government through the traditional approach is no longer plausible and hence, the general appeal of the public-private partnership framework. However, despite all the potentials, the public private partnership technique in Nigeria has not made an appreciable impact in closing the infrastructure gaps due to lack of access to long-term financing. It is against this back-drop that this study has sought to investigate how reforms of the legal and financial infrastructure could widen access to financing through innovative financial resource mobilization in scaling-up infrastructure development and service delivery to the teeming Nigeria population. Therefore, the central thesis of this study is that the inadequacy of appropriate laws and inefficient financial system are partly responsible for the huge financing gaps in the Nigeria‘s infrastructure market and with the legal and financial reforms, an enabling legal and financial environment that would open up space for resource mobilization through innovative financing techniques and sources will be created thereby widening access to long-term financing and increasing the appetite for private investment in the nation‘s public infrastructure assets and services. So, the overarching objective of this thesis is to explore how legal and financial system reforms can facilitate the development of financial models and instruments that can help mobilize financial resources to fund infrastructure and bridge the huge infrastructure financing gaps in Nigeria in a sustainable fashion. Given the infrastructure poverty that constrains economic growth and development in Nigeria, the outcomes of this proposed study would help inform the need for the legal and financial system reforms to unlock resources in addressing the problems of financing gaps in infrastructure projects development in Nigeria. Besides, such outcomes based on the Nigerian experience in infrastructure financing and development may be turned into valuable knowledge for policy –making and further research in Nigeria. Copyright
https://repository.up.ac.za/handle/2263/24525
Keywords: Foreign capital; Infrastructure; Legal reform; Nigeria; Public assets